Integrating responsible care into quality, environmental, health and safety management system: A strategy for Malaysian chemical industries - N Khairlida, Muhamad; Lee, Khai Ern *; Mazlin, Mokhtar *; Goh, Choo Ta (Elsevier, 2018)
A strategy for integrated management system of Quality, Environment, Health and Safety-Responsible Care (QEHS-RC) is proposed to improve the adoption and implementation of Responsible Care program in the chemical industries. This integrated management system provides a basis for the adoption and implementation of Responsible Care program in the chemical industries, moving beyond to a more holistic management system as it connects with other voluntary standards of which are ISO9001, ISO14001 and OHSAS18001. Taking Malaysian chemical industries as a case study, a comprehensive analysis has been conducted on the standards as well as Responsible Care code of management practices, indicating majority of the requirements of those standards are complimenting each other and there is a need to integrate all the standards into one single integrated and holistic management system to ensure chemical industries abide to the Plan-Do-Check-Act principles and sustainable development.